2017
DOI: 10.16965/ijpr.2017.146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Virtual Reality Versus Traditional Physical Therapy on Functional Balance in Children With Down Syndrome: A Randomized Comparative Study

Abstract: Background: Children with Down syndrome (DS) have difficulties with equilibrium, balance, and protective responses leading to delay in postural control and locomotion. Improvement in balance can produce greater stability while performing activities of daily living or work related tasks. Virtual reality (VR) allows individuals to experience activities and events similar to those they might encounter in real life. It can be used clinically to improve strength, range of motion, coordination, attention span, balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…Porém não visa a melhora da produção de força muscular de tronco, principalmente, para desempenhar um aumento da velocidade e diminuir o tempo de reação do COP. Ainda sobre o equilíbrio, o estudo de Ghafar et al 7 reforça a eficácia da RV na melhoria do equilíbrio funcional em estudo com 26 crianças com SD, no qual comparou-se o treinamento de equilíbrio com jogos Wii versus a fisioterapia tradicional e identificou-se melhorias significativas com o uso da RV.…”
Section: Discussionunclassified
“…Porém não visa a melhora da produção de força muscular de tronco, principalmente, para desempenhar um aumento da velocidade e diminuir o tempo de reação do COP. Ainda sobre o equilíbrio, o estudo de Ghafar et al 7 reforça a eficácia da RV na melhoria do equilíbrio funcional em estudo com 26 crianças com SD, no qual comparou-se o treinamento de equilíbrio com jogos Wii versus a fisioterapia tradicional e identificou-se melhorias significativas com o uso da RV.…”
Section: Discussionunclassified
“…Three studies [20,21,25] reported a low risk of bias. However, one study [16] showed unknown risk while the remaining studies demonstrated high-risk bias [5, 10-12, 15, 17-19, 22-24, 26-28].…”
Section: Blinding Of Outcome Assessmentmentioning
confidence: 99%
“…Among the eighteen experimental studies, fourteen studies were Randomized Controlled Trials; three were Quasi-experimental, while only one was Nonrandomized controlled trial. A study conducted by Alsakhawi et al [15], Eid et al [20], Ghafar et al [21], and Reis et al [22] investigated the effects of traditional/conventional physiotherapy with an adjunct intervention such as treadmill, core stability, isokinetic training, and virtual reality, and the investigation revealed that conventional therapy in combination with an adjunct intervention was more effective than solitary to improve balance among DS patients. Gheitasi et al [16] and Ghaeeni et al [26] showed the efficacy of core stability exercises, either alone or in combination with the swiss ball or resistance training, in improving static balance.…”
Section: Synthesized Findingsmentioning
confidence: 99%
See 2 more Smart Citations